Study of a simplified parametric control of split louver and its combination with bifacial PV technology in architectural environmental design - Alsukkar, Muna (2023)
Photovoltaic-integrated shading devices (PVSDs) involve energy conversion and daylight admission in buildings. This study investigates the application of PV glazing incorporated with an advanced parametric split louver daylighting system in a high-glazed façade. According to previous literature, simulations, and field experiments, the improved PV-integrated split louver for balancing solar energy's conflicting roles depends on the shading system's features (type, configuration, surface materials, and angle control) as well as the PV system's features (type, transparency, configurations, and efficiency). This study is comprehensive research comprising computer simulations and field experiments that develop a split louver and PV integrated system to achieve a functional architectural configuration of maximum daylighting performance and PV efficiency. Gradual steps using parametric modelling are developed and established progressively, ensuring the workflow's reliability. First, modifying the split louver configurations to improve the efficiency of the indoor daylight environment and, secondly, developing a simplified parametric control using the parametrically incremental slat angle. Further improvements, such as slat angle control, slat materials, and scheduled slat angles, meet the required useful daylight illuminance (UDI) ranges and enhance daylight distribution. Slat shapes and PV glass transmittance of the PV-integrated split louver affect daylight quality (uniformity and glare), in addition to its potential to increase the bifacial PV power output. The PV glazing-integrated split louver system provides more than 90% of the work plane area with recommended UDI150~750 lux levels for a longer duration, raising the uniformity level (Uo) to 0.70. Daylighting simulations were confirmed by field experiments in Nottingham, UK, with a strong correlation of 0.902. Furthermore, the bifacial PV-integrated split louver can increase power output, with experimental results showing a 12% increase with mirror slats and simulations indicating annual power output increases of 19% and 16% for Jordan and the UK, respectively.